Short-Term Effects of Operating Parameters and Wastewater Constituents on the Performance of Free-cell Candidatus Brocadia and Candidatus Scalindua Anammox Enrichment - KOCAMEMİ, BİLGE (My University, 2022)
Anammox, is a state-of-art nitrogen removal technology for domestic and industrial wastewater treatment. Anaerobic chemolithoautotrophic Anammox species are quite sensitive to operating parameters and various inorganic and organic compounds. Previous Anammox research was mainly on mixed cultures including Ca.Brocadia and/or Ca.Kuenenia species that are abundant in domestic wastewater. Little information exists about the mixed Anammox cultures including Ca.Scalindua species known as marine Anammox species that also present in WWTPs receiving sea-water infiltrated sewage, saline-rich wastewater in coastal cities and saline-rich industrial wastewater. In this study, the influence of operating parameters and organic and inorganic wastewater constituents on the performance of mixed suspended Ca.Brocadia and Ca.Scalindua Anammox enrichment was evaluated based on Specific Anammox Activity (SAA). Response surface methodology was used to model the relationship between pH, DO and temperature changes with SAA. Optimum pH and temperature were identified as 7.36 and 32.7(0)C, respectively. Short-term inhibitory (IC50) values of acetate, propionate and glucose were identified as 1000-1500, 3300 and 3600-5700 mg COD/L, respectively. NO2--N caused Anammox inhibition above 50 mg/l. IC50 values for SO42-, PO43--P and K+ were determined as 3500 mg SO42-/L, 1384 mg PO43--P/L and 2400 mg K+/L. The study provides a comprehensive insight into the tolerance of Ca.Brocadia and Ca.Scalindua enrichment against changing operational conditions and potential inhibiting compounds and facilitates optimization of operational strategies for the efficient performance of engineered Anammox systems. The findings will also contribute to future research activities that will focus on composite inhibitors and metabolic inhibition pathways.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; ÇEVRE BİLİMLERİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENVIRONMENTAL SCIENCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Doğa ve Peyzaj Koruma; Çevre Bilimi (çeşitli); Su Bilimi; Fizik Bilimleri; Yaşam Bilimleri; Nature and Landscape Conservation; Environmental Science (miscellaneous); Aquatic Science; Physical Sciences; Life Sciences; Anammox; Inhibition; Inorganics; Organics; Response Surface Methodology (RSM); Specific Anammox Activity (SAA); NITROGEN REMOVAL; LOW-TEMPERATURE; AMMONIUM; PH; INHIBITION; BATCH; BACTERIUM; GROWTH